Analysis of Performance Indicators for Optimization of Noninteger-Order Controllers - Zagorowska, Marta (Journal of circuits, systems, and computers, 2018)
Tuning noninteger-order controllers using parametric optimization remains a subject of ongoing research. One of the areas of focus concerns analysis of performance indicators ensuring desired behavior. In this paper we analyze linear, quadratic and quartic performance indicators as tools for finding parameters of PD α and PI γ controllers in R C ladder system of fourth order. Proposed optimization method uses the Laguerre Impulse Response Approximation (LIRA) method and ensures the stability of noninteger closed-loop system. The results were compared with classic PID controllers.